2020
DOI: 10.3389/fpsyt.2020.00844
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Effect of Ketamine Is Dampened by Concomitant Benzodiazepine Medication

Abstract: The rapid antidepressant effect of ketamine has become a breakthrough in the research and treatment of depression. Although predictive and modulating factors of the response to ketamine are broadly studied, little is known about optimal concurrent medication protocols. Concerning gamma-aminobutyric acid neurotransmission being a shared target for both ketamine and benzodiazepines (BZD), we evaluated the influence of BZD on the antidepressant effect of a single ketamine infusion in depressed patients. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
0
17
2
Order By: Relevance
“…(ie, taken between day −2 and day 2) did not augment or diminish the rapid, robust antidepressant effect observed after the first dose of esketamine in these patients (primary efficacy endpoint), which is specifically relevant in the setting of psychiatric emergencies. The findings from the ASPIRE studies do not support prior studies in which benzodiazepines were shown to attenuate the acute antidepressant effect of ketamine (Ford et al 17 [case study, n=1]; Frye et al 18 [post-hoc analysis, n=10]; Albott et al 19 [post-hoc analysis, n=14]; Andrashko et al 29 [n=47, excluded patients with suicidal risk assessed by clinical examination]). The disparity may be explained, at least in part, by the small sample size and uncontrolled methods of the ketamine studies and, perhaps, that the ketamine studies included patients who had TRD but were not in acute crisis.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…(ie, taken between day −2 and day 2) did not augment or diminish the rapid, robust antidepressant effect observed after the first dose of esketamine in these patients (primary efficacy endpoint), which is specifically relevant in the setting of psychiatric emergencies. The findings from the ASPIRE studies do not support prior studies in which benzodiazepines were shown to attenuate the acute antidepressant effect of ketamine (Ford et al 17 [case study, n=1]; Frye et al 18 [post-hoc analysis, n=10]; Albott et al 19 [post-hoc analysis, n=14]; Andrashko et al 29 [n=47, excluded patients with suicidal risk assessed by clinical examination]). The disparity may be explained, at least in part, by the small sample size and uncontrolled methods of the ketamine studies and, perhaps, that the ketamine studies included patients who had TRD but were not in acute crisis.…”
Section: Discussioncontrasting
confidence: 61%
“…In a post-hoc analysis of 10 patients with TRD given ketamine infusions twice weekly for up to 2 weeks, Frye et al 18 reported that non-responders received significantly higher mean daily doses of benzodiazepines than responders (≥50% decrease from baseline MADRS total score). Likewise, in a study of 47 patients with MDD and without suicidal risk who received a single ketamine infusion as an add-on to ongoing antidepressant treatment, Andrashko et al 29 reported a significantly lower response rate among those taking high-dose benzodiazepines (defined as >8 mg diazepam equivalent, n=13). And, in a post hoc analysis of 13 patients with TRD who received a ketamine infusion 3 times weekly for 2 weeks, Albott et al 19 reported no significant differences between benzodiazepine and non-benzodiazepine users in response or remission rates, or depression relapse rate over 4-week follow-up, but those taking benzodiazepine took significantly longer time to reach these outcomes and experienced significantly shorter therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were supported by reports of prolonged time to remission and shortened time to relapse in 13 patients with MDD receiving BZD compared to patients not concurrently receiving BZDs. 33 A recently published study 34 analyzing data from 2 previously conducted randomized, controlled trials reported that concurrent BZD use was a predictor of nonresponse in 47 patients with MDD to ketamine in a dose-dependent manner. Responders were receiving significantly lower doses of BZDs (7.7 ± 4.5 mg vs 32.1 ± 24.9 mg, diazepam equivalents) when compared to nonresponders.…”
Section: Resultsmentioning
confidence: 99%
“…As ketamine use increases, it is important to identify clinically significant pharmacodynamic drug-drug interactions. BZDs have been reported [31][32][33][34] to attenuate the effect of ketamine in MDD. While not all studies have reported evidence of this interaction, 35 given the persistence of this effect in the setting of heterogeneous data and proposed mechanism of ketamine in MDD, it seems likely that BZDs pose a pharmacodynamic interaction in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation